The cicadas (Hemiptera: Cicadidae) of Peru including the description of twenty-four new species, three new synonymies, and thirty-seven new records - Sanborn, Allen F. (Zootaxa, 2020)
The known cicada fauna of Peru is identified. Fidicinoides ptychodiropeda n. sp., Guyalna capnopteryx n. sp., G. chrysinothrix n. sp., G. dyticamazona n. sp., G. spilonotophora n. sp., Carineta acommosis n. sp., C. bitorquata n. sp., C. castaneopercula n. sp., C. dicrophryxothrix n. sp., C. digitata n. sp., C. nigrafissura n. sp., C. quadrofastigiata n. sp., C. rumipataensis n. sp., C. tingomariaensis n. sp., C. tricuspis n. sp., Herrera castanetorquata n. sp., H. cephalodigramma n. sp., H. chanchamayoensis n. sp., H. dentata n. sp., H. moyabambaensis n. sp., H. nigropercula n. sp., H. polygramma n. sp., H. quadrimacula n. sp., and H. viriventralis n. sp. are described as new. Three taxa, Cicada (Prunasis) pulcherrima var. a Stål, 1862a, C. (P.) pulcherrima var. b Stål, 1862a, and C. (P.) pulcherrima var. c Stål, 1862a are shown to be unavailable as well as junior synonyms of Prunasis pulcherrima (Stål, 1854) which is shown to be the correct name for the taxon over the preoccupied Cicada viridula Walker, 1850. The first records of Durangona tigrina Distant, 1911, Fidicina obscura Boulard & Martinelli, 1996, F. robini Boulard & Martinelli, 1996, Fidicinoides descampsi Boulard & Martinelli, 1996, F. determinata (Walker, 1858a), F. duckensis Boulard & Martinelli, 1996, F. pseudethelae Boulard & Martinelli, 1996, Proarna bergi (Distant, 1892a), P. dactyliophora Berg, 1879, P. strigicollis Jacobi, 1907, Guyalna aurora Ruschel, 2017, G. bicolor (Olivier, 1790), G. chlorogena (Walker, 1850), G. distanti (Goding, 1925), G. glauca (Goding, 1925), Majeorona aper (Walker, 1850), M. ecuatoriana Goding, 1925, M. truncata Goding, 1925, Orialella aerizulae Boulard, 1986b, Calyria cuna (Walker, 1850), Prunasis pulcherrima (Stål, 1854), Taphura boulardi Sanborn, 2011a, Carineta boulardi Champanhet, 1999, Carineta cearana Distant, 1906b, C. congrua Walker, 1858b, C. dolosa Boulard, 1986a, C. doxiptera Walker, 1858a, C. ecuatoriana Goding, 1925, C. gemella Boulard, 1986a, C. hamata Sanborn, 2019b, C. matura Distant, 1892b, C. pilifera Walker, 1858a, C. pilosa Walker, 1850, C. ventrilloni Boulard, 1986a, Herrera concolor Sanborn, 2019b, H. melanomesocranon Sanborn, 2019b, and H. phyllodes Sanborn, 2019b are provided. The records for Durangona tigrina Distant, 1911 are the first records of the genus Durangona Distant, 1911 and tribe Durangonini Moulds and Marshall, 2018 and the records for Prunasis pulcherrima (Stål, 1854) are the first for the genus Prunasis Stål, 1862a in Peru. Previous records of Zammara tympanum (Fabricius, 1803), Orialella boliviana (Distant, 1904b), Guyalna brisa (Walker, 1850) and Selymbria stigmatica (Germar, 1834) are considered to be misidentifications of Z. hertha Schmidt, 1919, O. aerizulae, G. dyticamazona n. sp. and S. madredediosensis Sanborn, 2019b, respectively, so that Z. tympanum, O. boliviana, G. brisa and S. stigmatica are removed from the cicada fauna of Peru. The Peruvian records of Dorisiana semilata (Walker, 1850) are shown to be due to an incorrect synonymy of D. metcalfi Sanborn & Heath, 2014 and the species is removed from the faunal list as well. Additional new records of Fidicinoides poulaini Boulard & Martinelli, 1996 are provided for Brazil and Guyalna chlorogena (Walker, 1850) for French Guiana to expand the known distribution of these species. The currently known Peruvian cicada fauna is comprised of 114 described species from 23 genera, eight tribes and three subfamilies with a 115% increase in the known cicada fauna provided here.